HANDBOOK OF RESEARCH ON APPLIED AI FOR INTERNATIONAL BUSINESS AND MARKETING APPLICATIONS (BUSINESS SCIENCE REFERENC, 2020)
Artificial intelligence (AI) describes machines/computers that mimic cognitive functions that humans associate with other human minds, such as learning and problem solving. As businesses have evolved to include more automation of processes, it has become more vital to understand AI and its various applications. Additionally, it is important for workers in the marketing industry to understand how to coincide with and utilize these techniques to enhance and make their work more efficient. The Handbook of Research on Applied AI for International Business and Marketing Applications is a critical s.